Cuidados paliativos e luto antecipatório: um estudo à luz do modelo Calgary de avaliação da família - Fernandes, Maria Andréa (2015)
Introduction: Palliative care is a philosophy of interdisciplinary care that aims to improve the quality of life of patients with life threatening diseases and families, acting in the physical, psychological, social and spiritual dimensions and bereavement support. This dissertation consists of two different articles, theoretical and empirical, whose central thematic focus between them are palliative care and bereavement. The first, theoretical, is entitled palliative and bereavement care: a bibliometric study. Objective: To analyze the scientific production published in online journals on palliative care and bereavement. Methodology: bibliometric review, whose sample consisted of articles published in the period from 2005 to 2014, available in LILACS, MEDLINE, IBECS, PubMed, SciELO and DOAJ. Results: We identified 48 studies disseminated in 37 journals, including the Journal Palliative Medicine Journal that was the most published on the subject, and the American Journal of Psychiatry showed the highest impact factor. Most of the papers produced by researchers of the medical area and predominated authors with the title of doctor. Conclusion: It was found that the production of knowledge involving palliative care and bereavement remains weak in the investigated period, which requires the expansion of knowledge on this theme and the issues surrounding it. The second study is a unique research, entitled: patients families Structure in palliative care about anticipatory grief: study based on the Calgary model. Objective: To analyze the structure of families of patients under palliative care about anticipatory grief in the light of Calgary Model. Methodology: This is a field of study with a qualitative approach, the participation of five families of patients under palliative care in a hospital in the city of João Pessoa - PB. To enable the collection of data, we used the genogram and eco-map. The empirical material was analyzed through the Calgary Model. Results: The results derived from research were described in two stages. The first, presented to the genogram and eco-map, from the stories told by the participating families of the research; and second, structural analysis of families in the light of the Calgary Model. Families highlighted the experience of a disease without therapeutic possibilities of cure as a process of profound loss, evidenced by the fragility that the disease imposes progressively and that lead them to experience a anticipatory grief. Conclusion: The utilization of family assessment model allowed for a larger view of the families included in the study and understanding of internal relations, external and context. Therefore, it is considered essential that nurses can work together with the family regarding the anticipatory grief to meet the needs and care of the person in palliative care. It is expected that the data obtained can support further research on the topic.